Capital Markets Union: Database of directives and regulations - Moritz Fabian Emlein; Eleonora Sfrappini; Lena Tonzer; Cristina Zgherea (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2022)
In 2015, the European Commission adopted the Capital Markets Union (CMU) action plan. The plan aims to deepen financial integration and harmonize international standards for investments within the European Union (EU) and it outlines several actions to be implemented in order to address twelve key priority areas. We assemble a database of the legislative acts that implement the CMU. The dataset includes a list of directives and regulations at the EU level with information on publication, entry into force, and transposition dates as well as brief descriptions. This information might be useful in empirical analyses assessing the effectiveness of components of the CMU.
Keywords: 330